Qualidade de vida relacionada à saúde em gestantes de alto risco - Gadelha, Ivyna Pires (2019)
Objective: To analyze the health-related quality of life of high-risk pregnant women. Materials and Methods: This is a quantitative, exploratory and cross-sectional study. The sample consisted of 276 pregnant women attending the high-risk prenatal service of the Maternity School Assis Chateaubriand, from August to November 2018. Data collection was performed through the application of the Medical Outcomes Study-36 Short- (SF-36) and The Mother Generated Index (MGI) Brazilian version, as well as a structured instrument including sociodemographic, clinical and obstetric data. The medical records were consulted for confirmation of the diagnosis. The data were compiled in Excel and analyzed using the statistical program Jamovi®, version 0.9. Results: As for the sociodemographic data, the sample consisted mainly of young adult women, with a median age of 30 years, who had a high school education and family income of 1 to 3 minimum salaries, lived with their partner, lived in the capital, were of brown race and catholic religion. Regarding clinical and obstetrical data, most of the women were in the third trimester of pregnancy, had up to two live children, did not plan for pregnancy, had inadequate body mass index, and used medications. Of the interviewees, the minority suffered hospitalization during pregnancy. Most indications for high-risk prenatal care were related to problems in the current pregnancy. The main diagnoses were: gestational diabetes mellitus, prematurity and chronic hypertension. According to the SF-36, the average quality of life was 47.2. The domain that obtained the worst quality of life among pregnant women was "limitation by physical aspects", while the one that obtained the best quality of life was "mental health". To plan for pregnancy and to have adequate nutritional status were factors associated with better health-related quality of life, while having live children, having a history of prematurity, having gestational diabetes mellitus or chronic hypertension, experiencing hospitalization during pregnancy and making use of medications were factors associated with poorer quality of life. The areas of life affected according to the MGI were: food, sleep, family relationship, psychological / emotional, relationship with partner, physical condition, work, satisfaction with pregnancy, financial and health. The average primary score for the positive comments was 8.39. One of the negative reviews was 3.38 and the one of the reviews both / none was 6.71. The total primary MGI score was 6.03, showing a relatively positive HRQOL assessment. Conclusion: It is concluded that health-related quality of life is multifactorial and, accordingly, care providers must know these factors, aiming to direct effective actions to promote quality of life, through the preparation of women to deal with pregnancy-puerperal process. Product: An original article was produced based on data from this research and an Integrative Literature Review.